Meta-Analysis on the Prevention of Sexual Abuse of Minors in the Catholic Church and in Other Institutions - Horten, Barbara; Dölling, Dieter (Kriminalističke teme, 2020)
The aim of the meta-analysis was to find evaluation studies on prevention programs on sexual abuse in institutions. Further, the meta-analysis asked for an effect of the prevention programs on the knowledge transfer on sexual abuse, the knowledge maintenance and anxiety and fear of sexual abuse. The meta-analysis included 39 evaluations of programs in the descriptive analysis. The analysis was based on studies with a pre-post comparison and an intervention group as well as a control group. Most of the studies used controlled assignment strategies for the intervention and control group. The analysis showed an effect of participating in a program on the knowledge transfer (0.61 (95 % CI = [0.45, 0.77]), and a long-term effect on the knowledge (0.58 (95 % CI = [0.09, 1.06]). Furthermore, the anxiety and fear to become a victim of sexual abuse was lower in the intervention groups than in the control groups (-0.23 (95 % CI = [-0.37, -0.08]). Therefore, the knowledge on sexual abuse could be increased by participation in a prevention program.